Draft Annual Plan 1989-90 Vol. III Part I Uttar Pradesh - Planning Commission (Planning Commission, 1988)
The Planning Commission vide their D. 0. letter no. PC (P) 2/88, dated September 13, 1988, have made changes in Sub-Sector, Major Head, Sub-Major Head and Minor Head, of development on account of which certain programmesj schemes have been shifted from one head to another head, resulting in changes in their outlays given in earlier documents.
Government of Uttar Pradesh, Planning Department